The local management of mobility associated with equipment: The mobility plan of the Escola d’Arquitectura del Vallès (Ciudades, 2017)
The local management of mobility associated with equipment: The mobility plan  of the Escola d’Arquitectura del Vallès
Keywords: mobility plan